An Integrative approach to treating porn addiction - Hariri, Heba Jamal (Journal of Educational and Psychological Sciences, 2023)
Porn Addiction has become one of the most widespread forms of addiction due to the addict’s easy access to pornographic materials via the Internet and its freedom (Wright & Randall, 2012). The effects of Porn addiction consumption devastate the individual in terms of his physical, psychological, and even social life. The spread of this addiction and its risks are matched by the weakness of integrated psychological treatment programs that appropriate to the Arab environment. In this study, the researcher designed an integrative psychotherapeutic model consisting of four treatment stages: To help pornography addicts recover, not only from the Porn addiction, but also from the roots that cause this addiction. The first stage is: preparation, the second stage: raising intellectual insight. The third stage: raising emotional insight. The fourth stage: maintaining balance and continuity. This intervention is based on theoretical and empirical literature regarding recovery from pornography consumption addiction and is based on two therapeutic methodologies: the cognitive-behavioral approach and insight- oriented therapy. This therapeutic methodology was applied to an experimental group of 11 addicts who attended the treatment program for 16 counseling sessions. The statistical results from the pre-posttest and the clinical interviews supported the effectiveness of this therapeutic intervention, not only in reducing the time spent consuming pornography, but also in raising emotional insight into the roots and causes that led to this addiction, supported by cognitive insight that contributed to revealing the unhealthy cognitive system that was formed. Over the years of addiction and how to correct it. The study recommended several recommendations, the most important of which is conducting more research on this methodology by introducing multiple demographic variables and training psychotherapy specialists in this integrative therapeutic approach.